Nutrient cycling in pristine and logged tropical rain forest : a study in Guyana - Brouwer, Leonard Cornelis (Tropenbos GeorgetownGY, 1996)
Focuses on the nutrient cycling in the tropical forest and the research area. Looks at the hydrochemical input-output budget of pristine forests and the impact of logging on nutrient losses. Examines throughfall, litterfall and decomposition. Presents conclusions and makes recommendations.